2009
DOI: 10.1051/0004-6361/200912397
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar disc in the Bok globule CB 26

Abstract: Context. Circumstellar discs are expected to be the nursery of planets. Grain growth within such discs is the first step in the planet formation process. The Bok globule CB 26 harbours such a young disc. Aims. We present a detailed model of the edge-on circumstellar disc and its envelope in the Bok globule CB 26. Methods. The model is based on HST near-infrared maps in the I, J, H, and K bands, OVRO and SMA radio maps at 1.1 mm, 1.3 mm and 2.7 mm, and the spectral energy distribution (SED) from 0.9 μm to 3 mm.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 51 publications
6
107
0
Order By: Relevance
“…The parameters derived for the disk model of this source are comparable to those for other circumstellar disks (M total = 0.07 M , see Madlener et al 2012;Gräfe et al 2011;Sauter et al 2009;Schegerer et al 2008;Wolf et al 2003Wolf et al , 2008. Wolf et al (2003) …”
Section: Appendix A: Atacama Large (Sub)millimeter Arraysupporting
confidence: 69%
See 1 more Smart Citation
“…The parameters derived for the disk model of this source are comparable to those for other circumstellar disks (M total = 0.07 M , see Madlener et al 2012;Gräfe et al 2011;Sauter et al 2009;Schegerer et al 2008;Wolf et al 2003Wolf et al , 2008. Wolf et al (2003) …”
Section: Appendix A: Atacama Large (Sub)millimeter Arraysupporting
confidence: 69%
“…The other dust grain radius range (a ∈ 0.005 μm, 0.25 μm ) represents the interstellar medium (Savage & Mathis 1979), which is important for this study because some young stellar objects (e.g. CB26, Sauter et al 2009) show a lack of large dust particles. The absorption properties of the dust depend on the grain size distribution.…”
Section: Radiative Transfermentioning
confidence: 99%
“…For instance, Szűcs et al (2010) investigated the Spitzer/IRAC and MIPS 24 μm photometries of ∼200 stars in the Chamaeleon I star-forming region and found that disks around lower mass stars (spectral type later than M4.75) are generally flatter than the case of higher mass stars (spectral type earlier than M4.5). Coherent multiwavelength modeling suggests a typical flaring index β ∼ 1.25 for T Tauri disks (Wolf et al 2003;Walker et al 2004;Sauter et al 2009;Madlener et al 2012;Gräfe et al 2013). Harvey et al (2012a) report PACS measurements of about 50 very low-mass stars and brown dwarfs with spectral types ranging from M3 to M9 in nearby regions.…”
Section: The Disk Properties Of the Targetsmentioning
confidence: 99%
“…This model has been successfully used to explain the observed SEDs of a large sample of young stellar objects and brown dwarfs (e.g., Wolf et al 2003;Sauter et al 2009;Harvey et al 2012a). For the dust in the disk, we assume a density structure with a Gaussian vertical profile…”
Section: Sed Modelingmentioning
confidence: 99%
“…Conclusions obtained using spectral energy distribution (SED) modeling are much more model-dependent and degenerate than using resolved images. Therefore, imaging of protoplanetary disks provides an independent check of SED modeling and a far less ambiguous method for studying the disk structure (e.g., Eisner et al 2009;Hughes et al 2009;Sauter et al 2009;Madlener et al 2012;Gräfe et al 2013). Various efforts to resolve the inner emission holes through direct imaging observations have been undertaken (e.g.…”
Section: Introductionmentioning
confidence: 99%